Morphological phylogeny and review of the generic classification of Colletinae (Hymenoptera: Colletidae). Issue 1 (24th November 2020) - Ferrari, Rafael R; Packer, Laurence
Abstract: The bee subfamily Colletinae includes 542 species, the vast majority of which (518 spp.) belong to Colletes . The generic placement of the remaining 24 species has been controversial, resulting in several classifications being proposed. Despite several recently published molecular phylogenies of Colletinae, it remains unknown (1) what morphological synapomorphies support the recognized genera, (2) in which direction some relevant functional traits (e.g. basitibial plate) have evolved and (3) whether morphology supports the available molecular data. Herein, we provide a morphological phylogeny of Colletinae, which was constructed through parsimony analyses of 186 characters. In total, 50 ingroup species were included representing all major lineages of Colletes (29 spp.), plus all but three of the non- Colletes species of Colletinae (21 spp.). Trees were estimated through equal weights and extended implied weighting. Both provide strong support for the monophyly of Colletinae and indicate that the subfamily is defined by four unique synapomorphies. Our results also confirm recent phylogenetic hypotheses showing that Colletinae can be subdivided into two major clades: one comprising the reciprocally monophyletic Mourecotelles and Xanthocotelles ; the other includes Colletes plus Hemicotelles, which are also reciprocally monophyletic. We also provide a fully illustrated key to facilitate generic identification of the Colletinae.